Commissioning of the world's first compact pencil‐beam scanning proton therapy system. (20th November 2017) - Pidikiti, Rajesh; Patel, Bijal C.; Maynard, Matthew R.; Dugas, Joseph P.; Syh, Joseph; Sahoo, Narayan; Wu, Hsinshun Terry; Rosen, Lane R.
Abstract: This paper summarizes clinical commissioning of the world's first commercial, clinically utilized installation of a compact, image‐guided, pencil‐beam scanning, intensity‐modulated proton therapy system, the IBA Proteus ® ONE, at the Willis‐Knighton Cancer Center (WKCC) in Shreveport, LA. The Proteus ® ONE is a single‐room, compact‐gantry system employing a cyclotron‐generated proton beam with image guidance via cone‐beam CT as well as stereoscopic orthogonal and oblique planar kV imaging. Coupling 220° of gantry rotation with a 6D robotic couch capable of in plane patient rotations of over 180° degrees allows for 360° of treatment access. Along with general machine characterization, system commissioning required: (a) characterization and calibration of the proton beam, (b) treatment planning system commissioning including CT‐to‐density curve determination, (c) image guidance system commissioning, and (d) safety verification (interlocks and radiation survey). System readiness for patient treatment was validated by irradiating calibration TLDs as well as prostate, head, and lung phantoms from the Imaging and Radiation Oncology Core (IROC), Houston. These results confirmed safe and accurate machine functionality suitable for patient treatment. WKCC also successfully completed an on‐site dosimetry review by an independent team of IROC physicists that corroborated accurate Proteus ® ONE dosimetry.